2014
DOI: 10.1038/bjc.2014.331
|View full text |Cite
|
Sign up to set email alerts
|

A putative OTU domain-containing protein 1 deubiquitinating enzyme is differentially expressed in thyroid cancer and identifies less-aggressive tumours

Abstract: Background:This study aimed to identify novel biomarkers for thyroid carcinoma diagnosis and prognosis.Methods:We have constructed a human single-chain variable fragment (scFv) antibody library that was selected against tumour thyroid cells using the BRASIL method (biopanning and rapid analysis of selective interactive ligands) and phage display technology.Results:One highly reactive clone, scFv-C1, with specific binding to papillary thyroid tumour proteins was confirmed by ELISA, which was further tested agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 32 publications
(34 reference statements)
1
28
0
Order By: Relevance
“…The PGLI-M3 positivity for IgM was detected in MB clinical forms (BB, BL, and LL) follows similar patterns observed for the native PGL-I. Our study observed an average seropositivity of 78% in MB forms, while in the literature the positivity varied from 51.2 to 97.4% for the native PGL-I (Carneiro et al, 2014) and 76.36% for synthetic derivatives with ND-O-HSA ELISA (Lobato et al, 2011). The total positivity including all clinical forms was also similar, for example the lateral flow system (ML-Flow) using NT-P-HSA as antigen presented 97.4% (Bührer-Sékula et al, 2003), which corroborates our findings that showed 92.5% positivity using the PGLI-M3.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The PGLI-M3 positivity for IgM was detected in MB clinical forms (BB, BL, and LL) follows similar patterns observed for the native PGL-I. Our study observed an average seropositivity of 78% in MB forms, while in the literature the positivity varied from 51.2 to 97.4% for the native PGL-I (Carneiro et al, 2014) and 76.36% for synthetic derivatives with ND-O-HSA ELISA (Lobato et al, 2011). The total positivity including all clinical forms was also similar, for example the lateral flow system (ML-Flow) using NT-P-HSA as antigen presented 97.4% (Bührer-Sékula et al, 2003), which corroborates our findings that showed 92.5% positivity using the PGLI-M3.…”
Section: Discussionsupporting
confidence: 85%
“…The selection of synthetic peptide PGLI-M3 binding antibodies was done using a scFv library fused to PIII protein (Carneiro et al, 2014) according to the protocol described elsewhere (Barbas, 2001). The combinatory scFv library, obtained from an RNA pool of non-infected individuals, with a 2 × 10 8 diversity, was amplified using a phage helper properly titrated.…”
Section: Antibody Phage Displaymentioning
confidence: 99%
“…Recently, OTUB1 is reported to be overexpressed in non-small-cell lung carcinoma (NSCLC) and promotes RAS activation by inhibiting RAS monoubiquitination [132]. Moreover, high expression of OTUD1 is also seen in thyroid carcinoma signifying its oncogenic nature [133]. On the other hand, OTUD5 is linked to apoptosis and is involved in stabilization and activation of p53, suggesting a possible tumor suppressive role [134].…”
Section: Usp30 Usp33mentioning
confidence: 99%
“…2009 ). The expression of OTUD1 is highly up-regulated in various carcinomas of the thyroid and could potentially be used as a biomarker to distinguish between cancerous samples ( Carneiro et al . 2014 ).…”
Section: Endocrine Cancersmentioning
confidence: 99%